ANALISIS YURIDIS TRANSAKSI SEMU DALAM PERDAGANGAN EFEK BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1995 TENTANG PASAR MODAL - Irwanto (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2022)
Irwanto, Moch. Zairul Alam, Ranitya Ganindha Fakultas Hukum Universitas Brawijaya e-mail: irwanto.ksi@gmail.com ABSTRAK Pertumbuhan perekonomian di Indonesia yang terus berkembang menjadikan Indonesia sebagai negara incaran Para investor untuk melakukan investasi. Jadi pasar modal Indonesia juga harus dikembangkan agar dapat mengimbangi pesatnya kondisi pasar modal sekarang. tetapi undang-undang pasar modal Indonesia yang dibuat pada tahun 1995 sudah tidak sesuai dengan kondisi pasar modal dengan modernitas saat ini. mengakibatkan terdapat celah yang bisa dimanfaatkan oleh investor untuk curang. Transaksi Semu dalam Manipulasi pasar pada akhirnya dapat merugikan banyak investor lain. Berdasarkan latar belakang penelitian di atas, maka dirumuskan 2 (dua) rumusan masalah untuk diuraikan, difahami, dan dianalisis sesuai dengan ketentuan undang-undang Nomor 8 Tahun 1995 tentang pasar modal (UUPM) Rumusan masalah pertama yaitu Bagaimana analisis kelemahan pengaturan Transaksi Semu berdasarkan Undang-Undang Nomor 8 tahun 1995 tentang Pasar Modal. Rumusan masalah kedua adalah Bagaimana formulasi pengaturan terkait transaksi semu yang memadai dalam ketentuan pasar modal di indonesia. Penelitian ini menggunakan jenis penelitian hukum metode yuridis normatif dengan pendekatan penelitian yaitu dan undang-undang, konseptual dan perbandingan. Bahan hukum primer diperoleh dari undang-undang pasar modal di Indonesia dan peraturan pendukung. bahan hukum sekunder diperoleh dari buku, jurnal, dan putusan pengadilan. serta bahan hukum tersier dari penelitian terkait, makalah, kamus, Bahasa Hukum, materi seminar atau internet. Dengan semakin maraknya perbuatan manipulasi pasar terutama itu dalam perbuatan Transaksi Semu di Pasar Modal mengimbangi perkembangan pesat kegiatan di Pasar Modal dengan mengikuti standar internasional, maka perlu dibuat formulasi baru peraturan Transaksi Semu di UUPM mengenai ruang lingkup dan sanksi Transaksi Semu. mengenai ruang lingkup tindakan, penafsir, kelengkapan peraturan, sanksi remidi serta pembuktiannya dengan metode civil penalty. Kata Kunci : Analisis Yuridis, Transaksi Semu, Perdagangan Efek, Penerapan Undang-Undang. ABSTRACT The growing economy in Indonesia has attracted other countries as prospective investors. This condition indicates that the capital market in Indonesia should also be developed to keep up with the vastly growing market conditions these days. However, the Capital Market Law of 1995 is no longer relevant to the current conditions of the capital market, leaving an opportunity for investors to cheat. Pseudo transactions intended to manipulate markets, for example, could disadvantage investors. Departing from this issue, this research aims to investigate the two problems: how is the weak regulation on pseudo transactions according to Law Number 8 of 1995 concerning Capital Markets analyzed and how is the accommodating regulation concerning pseudo transactions formulated in capital markets in Indonesia. This research employed normative-juridical methods, statutory, conceptual, and comparative approaches. The primary legal materials were obtained from capital market law in Indonesia and other supporting regulations, while the secondary ones were from books, journals, and court decisions. The tertiary materials consisted of papers, dictionaries, legal terms, and seminars on the Internet. The research concludes that the growing trends of market manipulation regarding pseudo transactions in capital markets and the vastly growing activities in capital markets need to take into account the adjustment to international standards and the formulation of new regulatory provisions concerning pseudo transactions in the Capital Market Law in terms of the scope and the sanctions imposed on the transactions. On the other hand, the scope of the actions, interpretations, complete regulations, remedial sanctions, and proof can refer to a civil penalty ABSTRACT The growing economy in Indonesia has attracted other countries as prospective investors. This condition indicates that the capital market in Indonesia should also be developed to keep up with the vastly growing market conditions these days. However, the Capital Market Law of 1995 is no longer relevant to the current conditions of the capital market, leaving an opportunity for investors to cheat. Pseudo transactions intended to manipulate markets, for example, could disadvantage investors. Departing from this issue, this research aims to investigate the two problems: how is the weak regulation on pseudo transactions according to Law Number 8 of 1995 concerning Capital Markets analyzed and how is the accommodating regulation concerning pseudo transactions formulated in capital markets in Indonesia. This research employed normative-juridical methods, statutory, conceptual, and comparative approaches. The primary legal materials were obtained from capital market law in Indonesia and other supporting regulations, while the secondary ones were from books, journals, and court decisions. The tertiary materials consisted of papers, dictionaries, legal terms, and seminars on the Internet. The research concludes that the growing trends of market manipulation regarding pseudo transactions in capital markets and the vastly growing activities in capital markets need to take into account the adjustment to international standards and the formulation of new regulatory provisions concerning pseudo transactions in the Capital Market Law in terms of the scope and the sanctions imposed on the transactions. On the other hand, the scope of the actions, interpretations, complete regulations, remedial sanctions, and proof can refer to a civil penalty